1994
DOI: 10.1007/bf00195513
|View full text |Cite
|
Sign up to set email alerts
|

Thrombolysis of a partially occluding superior mesenteric artery thromboembolus by infusion of streptokinase

Abstract: Occlusion of the superior mesenteric artery by thromboembolism is an uncommon cause of acute intestinal ischemia but carries a high mortality. This report describes a case of mesenteric thromboembolism in an 80-year-old woman treated successfully by selective low-dose infusion of streptokinase over 17 hours. Only twelve previous cases have been reported in the world literature. Selective thrombolytic therapy appears effective in the treatment of mesenteric thromboembolism, particularly in elderly patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…Ottinger [3] reported a mortality rate of 85% for 103 patients with acute occlusion of the SMA. Other reports [8][9][10][11][12][13][14] indicated that the clinical condition of the patients necessitated the use of fibrinolysis within 12 hr of onset of clinical signs and symptoms, because the mortality rate increases after more than 24 hr from onset [2]. Indication of intraarterial thrombolysis remains controversial, however.…”
Section: Discussionmentioning
confidence: 98%
“…Ottinger [3] reported a mortality rate of 85% for 103 patients with acute occlusion of the SMA. Other reports [8][9][10][11][12][13][14] indicated that the clinical condition of the patients necessitated the use of fibrinolysis within 12 hr of onset of clinical signs and symptoms, because the mortality rate increases after more than 24 hr from onset [2]. Indication of intraarterial thrombolysis remains controversial, however.…”
Section: Discussionmentioning
confidence: 98%
“…The appropriate therapeutic option is guided by the etiology of ischemia. A less well established approach is local infusion of thrombolytic therapy through angiographic catheter, which has been successful in a selected number of reports [51][52][53]. Treatment decision is guided by the presence or absence of peritoneal signs, partial or complete arterial obstruction, and on whether the location of the embolus proximal to the origin of the ileo-colic artery or in more distal branches.…”
Section: Treatmentmentioning
confidence: 99%
“…Scheduled "second look" operations, 24 to 48 hours after the initial procedure, are the best way to avoid both excessive resection of potentially viable bowel and failure to resect nonviable intestine. Despite limited data, percutaneous treatment (lytic therapy; balloon angioplasty or stenting or both) of the arterial obstruction is reasonable given the high mortality associated with the standard operative approach (223)(224)(225). However, because most patients with acute intestinal ischemia have at least some nonviable intestine at the time of presentation, most will still require laparotomy, and surgical assessment of intestinal viability may be required even if percutaneous therapy is successful in relieving the obstruction.…”
Section: Computed Tomographic (Ct) Scanningmentioning
confidence: 99%